El narrador no confiable en Robert Walser y Carlo Emilio Gadda: Una lectura comparada (El Hilo de la Fabula, 2021)
In this article we will explore some points in common between the writers Robert Walser and Carlo Emilio Gadda; specifically, the use of the unreliable narrator in the novels Der Räuber (1925) and La cognizione del dolore (1963/1970). In this way, we will argue how the appearance of the unreliable narrator is in line with the avant-garde and experimental narrative program of these two authors whose contribution was decisive for 20th century literature.
Keywords: Robert Walser; Carlo Emilio Gadda.; Unreliable narrator